The Influence of Farmer’s Attitudes in the Decision to Use Chemical Pesticides in the Protection of Horticultural Crop Cayenne Pepper (Capsicum Frutescens L.) in Bayan District, North Lombok Regency - I GN Aryawan Asasandi; M. Yusuf; Fadli (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2024)
Farmer's attitudes are the main factor in deciding to carry out something, including decisions regarding the use of pesticides in farming. The objectives of this research are (1) analyzing the influence of farmers' attitudes on decisions regarding the use of chemical pesticides in protecting cayenne pepper plants and (2) finding a model approach to reducing the use of chemical pesticides on cayenne pepper plants. This study uses descriptive methods and quantitative research types. The study uses a comparative type. The research location was in Bayan District as a center for the development of cayenne pepper in North Lombok Regency. Data analysis uses SEM (Structural Equation Model) with PLS (Partial Least Squares). The results of the research are: (1) The influence of farmers' attitudes, consisting of affective and conative, influences farmers' decisions in protecting cayenne pepper plants using chemical pesticides. Meanwhile, the cognitive aspect does not influence farmers' decisions. (2) The model that can be proposed is to reduce the use of chemical pesticides; it is necessary to maximize farmers' attitudes through socialization and training, especially those that can touch farmers' cognition (knowledge).